ANALYSIS OF THE USE “WHO AM I GAME” IN LEARNING DESCRIPTIVE TEXT TO INCREASE STUDENTS WRITING SKILLS OF JUNIOR HIGH SCHOOL 30 PALEMBANG - Nailah Putri, Ariqah; Veto Mortini , Asti; Pratiwi , Etty (Esteem Journal of English Education Study Programme, 2024)
The objective of this study was to investigate the impact that playing the game "Who am I" has on the students' capacity to comprehend descriptive literature at Junior High School 30 Palembang. It was evaluated using the game "Who am I" whether or not students were successful in their enthusiasm in learning English. In order to be successful in teaching English in Indonesia, students need to be able to communicate with native speakers of the language and be aware that English is used as a second language in a number of nations. There are certain areas of the country, such as commerce and education, that serve as a conduit to other languages. The research method that was utilized in this approach was qualitative, and it utilized procedures for data gathering such as observation, interviews, and direct documentation at Junior High School 30 Palembang. The approach of playing the "Who am I" game was utilized as a result of this research. Would be able to.